2021
DOI: 10.1186/s12891-020-03907-w
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth sounds a bit challenging, but it has potential: participant and physiotherapist experiences of gym-based exercise intervention for Achilles tendinopathy monitored via telehealth

Abstract: Background Although telehealth is becoming more popular for delivery of care for individuals with musculoskeletal pain, to our knowledge telehealth has not been used to manage Achilles tendinopathy. This research aimed to explore the experience of participants and physiotherapists with gym-based exercise interventions for Achilles tendinopathy monitored via videoconference. Methods A qualitative, interpretive description design was performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 39 publications
1
36
0
1
Order By: Relevance
“…At follow-up, semi-structured interviews were conducted via videoconferencing by a study investigator (PJ) with expertise and experience in qualitative research [ 18 , 19 ]. A set list of questions was designed to elicit responses to identify enablers and barriers of participating in the home-based exercise snacking intervention (S1).…”
Section: Methodsmentioning
confidence: 99%
“…At follow-up, semi-structured interviews were conducted via videoconferencing by a study investigator (PJ) with expertise and experience in qualitative research [ 18 , 19 ]. A set list of questions was designed to elicit responses to identify enablers and barriers of participating in the home-based exercise snacking intervention (S1).…”
Section: Methodsmentioning
confidence: 99%
“…Over the past decade, evidence to support the efficacy and acceptability of physiotherapy care delivered via telehealth has been growing (Kumar et al., 2022; Seron et al., 2021; Suso‐Martí et al., 2021; Zischke et al., 2021). Although telehealth may encompass care delivered via wearable devices and virtual reality and other technologies (Suso‐Martí et al., 2021), most physiotherapy research to date has focussed on real‐time (synchronous) consultations between a physiotherapist and a patient via telephone or videoconferencing as this reflects how most telehealth‐delivered physiotherapy care occurs in practice (Bennell et al., 2021; Cottrell & Russell, 2020; Hasani et al., 2021; Wong et al., 2020). Research suggests that physiotherapy care delivered via telehealth is effective within a variety of patient populations, including, for example, patients with osteoarthritis (Azma et al., 2018; Bennell et al., 2017, 2022; Hinman et al., 2020), non‐specific low back pain (Dario et al., 2017; Dario & Simic, 2021), hip replacements (Pastora‐Bernal et al., 2017) and other musculoskeletal conditions such as patellofemoral joint pain (Albornoz‐Cabello et al., 2021), as well as for patients requiring rehabilitation following knee arthroplasty (Jiang et al., 2018; Shukla et al., 2017) or shoulder surgery (Eriksson et al., 2009; Kane et al., 2020) or for pulmonary conditions (Michaelchuk et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This has revealed that we need innovations in rehabilitation and exercise practices. Studies on young individuals, who can use new technology really well, are extremely insufficient (Hasani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%